Thou shalt not smoke: Content and context in the Lord"s Resistance Army"s concept of the Ten Commandments - Holter, Knut (HTS teologiese studies, 2019)
With the Ten Commandments as a case, the overall focus of this article is how a reader’s a priori concept of a text influences how he or she allows textual content and interpretive context to interact. The frame of the article is the claim by the so-called Lord’s Resistance Army (LRA) in Uganda that they will establish a society built on the Ten Commandments, a claim that raises questions about what they mean with this reference to ‘Ten Commandments’. The article falls into two parts. The first part surveys some examples from the history of interpretation of the Ten Commandments, demonstrating contextual and terminological fluidity both in their biblical versions and in their postbiblical history of interpretation. With this insight, the second part discusses how LRA refers to the Ten Commandments in ways that demonstrate that the very concept ‘Ten Commandments’ is stronger than the details of their content. This enables the LRA to form ‘new commandments’ fitting with their ideology and struggle.